2009
DOI: 10.1093/cercor/bhp011
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Brain Activation and Brain Structure in Normally Developing Children

Abstract: Dynamic changes in brain structure, activation, and cognitive abilities co-occur during development, but little is known about how changes in brain structure relate to changes in cognitive function or brain activity. By using cortical pattern matching techniques to correlate cortical gray matter thickness and functional brain activity over the entire brain surface in 24 typically developing children, we integrated structural and functional magnetic resonance imaging data with cognitive test scores to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 47 publications
6
65
0
Order By: Relevance
“…Similarly, thinner parietal cortices were reported to be associated with better performance in verbal learning and memory, visuospatial functioning, and spatial planning and problem solving (Squeglia et al, 2013). Furthermore, thinner, that is, more mature, cortical gray matter seems to be associated with more mature patterns of brain activity and increased functional selectivity in cognitive tasks (Wendelken, OʼHare, Whitaker, Ferrer, & Bunge, 2011;Lu et al, 2009). Thus, pruning processes might be of special importance in younger children at the beginning of reading development and may lay out the basic neural foundation of the reading network.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, thinner parietal cortices were reported to be associated with better performance in verbal learning and memory, visuospatial functioning, and spatial planning and problem solving (Squeglia et al, 2013). Furthermore, thinner, that is, more mature, cortical gray matter seems to be associated with more mature patterns of brain activity and increased functional selectivity in cognitive tasks (Wendelken, OʼHare, Whitaker, Ferrer, & Bunge, 2011;Lu et al, 2009). Thus, pruning processes might be of special importance in younger children at the beginning of reading development and may lay out the basic neural foundation of the reading network.…”
Section: Discussionmentioning
confidence: 97%
“…However, there may be later costs associated with premature maturation of negative amygdala-mPFC functional connectivity. Previous research has demonstrated that a neotenized brain (one showing slower cortical development) has been associated with optimized behavioral outcomes in adulthood (e.g., higher IQ) (36), perhaps because a prolonged period of immaturity allows for more opportunity to learn from the environment and to increase adult efficiency (37,38). Although the positive amygdalamPFC coupling observed early in typical development is not well understood, it may serve an important function that is abbreviated or missed following early life stress, which could have consequences for later circuit optimization.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, thinner cortices in children and adolescents relate to either increased or decreased activation, depending on brain location and performance improvement. 15 Similarly, thinner right inferior frontal cortices are linked to increased right inferior frontal activation in children and adolescents. 16 However, in a larger sample of adolescents no relation is observed between cortical and functional maturation-with authors cautioning against pre-assuming such an association.…”
Section: General State Of Developmental Cognitive Neurosciencementioning
confidence: 99%